2016
DOI: 10.1002/lsm.22578
|View full text |Cite
|
Sign up to set email alerts
|

In vivo endoscopic Doppler optical coherence tomography imaging of the colon

Abstract: Background and Objective Colorectal cancer remains the second deadliest cancer in the United States. Several screening methods exist, however detection of small polyps remains a challenge. Optical coherence tomography has been demonstrated to be capable of detecting lesions as small as 1 mm in the mouse colon, but detection is based on measuring a doubling of the mucosa thickness. The colon microvasculature may be an attractive biomarker of early tumor development because tumor vessels are characterized by irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 34 publications
(46 reference statements)
0
12
0
Order By: Relevance
“…In addition to ultrahigh-resolution morphology, we will also explore the possibilities to quantify hemodynamics-related parameters using our vis-OCT colposcopic imaging. 17,30,37,43 Disclosures Hao F. Zhang, Cheng Sun, and Wenzhong Liu have financial interests in Opticent Health, which, however, did not support this work.…”
Section: Discussionmentioning
confidence: 85%
“…In addition to ultrahigh-resolution morphology, we will also explore the possibilities to quantify hemodynamics-related parameters using our vis-OCT colposcopic imaging. 17,30,37,43 Disclosures Hao F. Zhang, Cheng Sun, and Wenzhong Liu have financial interests in Opticent Health, which, however, did not support this work.…”
Section: Discussionmentioning
confidence: 85%
“…Hariri et al showed that Polarization Sensitive OCT (PS-OCT) has a potential to help in differentiation between lung tumor and fibrosis and Kiseleva et al used PS-OCT to diagnose mucosal pathologies in in-vivo human bladders (Hariri et al 2013 ; Kiseleva et al 2015 ). In addition, other functional OCT variants, such as Doppler-OCT that visualizes tissue vasculature and spectroscopic OCT that differentiates tissue types based on signal attenuation, as well as multimodality approaches are currently a topic of research (Barwari et al 2011 , 2012 ; Mavadia et al 2012 ; Welge and Barton 2017 ).…”
Section: General Conclusion and Future Perspectivesmentioning
confidence: 99%
“…In prior work, several research groups have demonstrated promising results that suggest OCT, an established high resolution imaging modality [9][10][11][12][13], may address the shortcomings of traditional camera endoscopy in the upper gastrointestinal tract [14][15][16] or large intestine [17][18][19]. OCT has been shown to accurately differentiate abnormal from normal tissue in multiple organs as an "optical biopsy" tool [20][21][22][23] in both murine and human colorectal models [24][25][26][27].…”
Section: Ivyspringmentioning
confidence: 99%